Oral biofilms: a reservoir of transferable, bacterial, antimicrobial resistance. Issue 12 (December 2010) - Roberts, Adam P; Mullany, Peter
Oral microbes are responsible for dental caries and periodontal diseases and have also been implicated in a range of other diseases beyond the oral cavity. These bacteria live primarily as complex, polymicrobial biofilms commonly called dental plaque. Cells growing within a biofilm often exhibit altered phenotypes, such as increased antibiotic resistance. The stable structural properties and close proximity of the bacterial cells within the biofilm appears to be an excellent environment for horizontal gene transfer, which can lead to the spread of antibiotic resistance genes amongst the biofilm inhabitants. This article will present an overview of the different types and amount of resistance to antibiotics that have been found in the human oral microbiota and will discuss the oral inhabitants' role as a reservoir of antimicrobial resistance genes. In addition, data on the genetic support for these resistance genes will be detailed and the evidence for horizontal gene transfer reviewed, demonstrating that the bacteria inhabiting the oral cavity are a reservoir of transferable antibiotic resistance